The answer will be A. 471/11. Hope it help!
Answer:
Step-by-step explanation: WELL i cant help lm really sorry
Answer:
-2x + 6
Step-by-step explanation:
Step 1: Define
f(x) = 3x + 2
g(x) = 4 - 5x
Step 2: Find f(x) + g(x)
3x + 2 + 4 - 5x
-2x + 6
Answer:
x = 0
Step-by-step explanation:
You know the answer to this because you know the identity element for addition is 0: 5 + 0 = 5.
__
Or, you can make use of the addition property of equality and add -5 to both sides of the equation:
5 - 5 + x = 5 - 5
x = 0 . . . . . . . . . . simplify
Answer:
-63/2
Step-by-step explanation:
6( -5 1/4)
= 6(-21/4)
= -63/2